Indonesia : Sustaining Growth During Global Volatility. (International Monetary Fund, 2012)
Over the past decade, Indonesia has developed into an important regional and global economy, as well as an active participant in the G20. The chapters in this book document the substantial improvements in the quality of macroeconomic policy that Indonesia has achieved, while also clearly laying out an agenda of measures that should be taken to safeguard these gains and further lower vulnerabilities going forward. Rather than just demonstrating progress in key macroeconomic indicators, the contributors have delved into the ways that global volatility, especially since 2008, has affected Indonesia and how that country has adjusted its policies to meet the new challenges.